Scavenging insects found on a carcass of the endangered Galápagos sea lion Zalophus wollebaeki - Román, Andrea C.; Chicaiza-Herrera, Janna; Betancourt-Cargua, Lenyn; Pinto, C. Miguel (Therya Notes, 2023)
Zalophus wollebaeki is a species of sea lion endemic to the Galápagos Islands. Dead bodies of Galápagos sea lions are frequently found on beaches, but little is known about their decomposers. The objective of this study is to report a sample of insects found on a sea lion carcass. In November 2022, a dead Z. wollebaeki was found on Caamaño Islet, from which we collected and identified pupae and adult of scavenging insects. We found 2 species of beetles and 1 of fly. The specimens were identified as Phaleria manicata (Coleoptera: Tenebrionidae), Dermestes ater (Coleoptera: Dermestidae), and Galopagomyia inoa (Diptera: Sarcophagidae). Phaleria manicata and G. inoa are reported for first time on a carcass of a sea lion. In the Galápagos, scavenging insects and their role in the decomposition process are little known. Consequently, more studies should focus on understanding the ecological role of scavenger communities in the different ecosystems of the Galápagos Islands.